2013
DOI: 10.1002/phy2.13
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of the preferred directions of the ON-OFF direction selective ganglion cells in the rabbit retina requires refinement after eye opening

Abstract: The ON–OFF direction selective ganglion cells (DSGCs) in the mammalian retina respond differentially for an object moving in different directions. DSGCs can be further segregated into four functional subtypes, namely those responsible for the detection of motion in the superior, inferior, anterior, and posterior directions of the visual field. Although it has been known that the basic neural circuit of direction selectivity is established at around the time of eye opening, it is less known if the four DSGC sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 67 publications
2
16
2
Order By: Relevance
“…A recent study demonstrated that at eye-opening in both rabbit and mouse, the distribution of preferred directions was uniformly distributed, rather than showing segregation along the four cardinal axes, indicating that a process of refinement in the preferred direction occurs after eye-opening (Chan & Chiao, 2013). They also found a slight degree of anisotropy in the distribution of preferred directions in dark reared animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that at eye-opening in both rabbit and mouse, the distribution of preferred directions was uniformly distributed, rather than showing segregation along the four cardinal axes, indicating that a process of refinement in the preferred direction occurs after eye-opening (Chan & Chiao, 2013). They also found a slight degree of anisotropy in the distribution of preferred directions in dark reared animals.…”
Section: Discussionmentioning
confidence: 99%
“…The development of direction selective circuits does not require visual experience because direction selectivity is already established at eye opening (Elstrott et al , 2008; Chan & Chiao, 2008; Chen et al , 2009; Wei et al , 2011; Chen et al , 2014), though several features of DSGCs are immature at these early ages (Chan & Chiao, 2008, 2013; Chen et al , 2014). However, spontaneous activity may play a role.…”
Section: Introductionmentioning
confidence: 99%
“…To compare the extent of clustering, we computed the silhouette value, with higher silhouette values indicating an appropriate number of clusters [20,21] (see Supplemental Information). Adult retinas displayed significantly higher silhouette values for 3 and 4 specific clusters for the ON and the ON-OFF DSGCs, respectively than a random distribution of preferred directions (0.91 and 0.89).…”
Section: Clustering Of Dsgc Preferred Directions Along Cardinal Axes mentioning
confidence: 99%
“…They comprise four subtypes, each preferring one of four cardinal directions 1618 . The polar distribution of directional preferences among ON‐OFF‐DSGCs appears cruciform, with four lobes separated by 90° (Fig.…”
Section: Introductionmentioning
confidence: 99%